341 Structure Proteins of Hepatitis C Induce miR-494-3p and miR942-3p Expression. (11th January 2018) - Lin, Tsun-Mei; Lin, Chih-Wen; Eng, Hock-Liew
Abstract: Introduction: Hepatitis C virus (HCV) infection, estimated in 3% of the world's population, remains a major risk factor for chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. Based on the recognition of single-stranded viral RNA, TLR7 and TLR8 have been suggested to play important roles in antiviral immune responses to HCV. The miRNAs, endogenously expressed small noncoding RNAs, are known to promote mRNA degradation and block protein translation. In the present study, the specific candidate miRNAs that influence HCV protein-modulated TLR7/8 expression and subsequent signal modulation were investigated. Methods: miRNA microarray analysis was performed to screen for the miRNAs expression in HCV structure proteins (core, E1, and E2) stably transfected HepG 2 cells, and miRBase was used to predict the interaction between these miRNAs and TLR7/8 gene. miR-494-3p and miR942-3p were identified and validated. A total of 100 serum samples (30 samples from controls, 70 samples from HCV-infected patients) were collected. The levels of the two, miR-494-3p and miR942-3p, were then detected by probe-based stem-loop quantitative reverse-transcriptase PCR. Results: We found that the expression of serum miR-494-3p and miR942-3p was distinctly increased in HCV patients compared with controls (mean ± SEM: 917.7 ± 192.2 vs 32.5 ± 14.2, P < .001 and 1615.0 ± 516.3 vs 8.0 ± 5.4, P < .001). In addition, interferon treatment significantly decreased miR942-3p expression in HCV patients (mean ± SEM: 67200 ± 55000 vs 263400 ± 195900, P = .03). Conclusion: The expression of miR-494-3p and miR942-3p in serum were significantly up-regulated in patients with HCV infection. However, the modulation mechanisms of miR494-3p and miR942-3p on TLR7/8 need further investigation.